"Nose‐metrics" of wild southern elephant seal (Mirounga leonina) males using image analysis and geometric morphometrics. (10th March 2019) - Galimberti, Filippo; Sanvito, Simona; Vinesi, Maria Chiara; Cardini, Andrea
Abstract: The elephant seal (genus Mirounga ) proboscis is a textbook example of an exaggerated secondary sexual trait, whose function is debated. The proboscis can be related to sexual status advertising, emission of aggressive vocalizations, and/or female mating choice. The study of the proboscis is complicated, because it is a soft trait that needs to be studied when males vocalize and it is thus expanded. Here, we combined field stimulation experiments, 2D photogrammetry, and geometric morphometrics, to study the proboscis of wild elephant seals in natural conditions. The goal of our study was twofold: (a) to demonstrate that photogrammetry and geometric morphometrics can be effectively applied in the field to wild, large, non‐sedated mammals; (b) to study the proboscis shape development during maturation. We found that it is possible to accurately estimate the proboscis size and shape using photographs of vocalizing males taken in the field. Moreover, we showed that mature and non‐mature males differ not only in proboscis size but also in its shape, a difference that is largely allometric and can have important effects on the frequency structure and individual signature of male vocalizations. These results open new avenues for future research on this enigmatic structure, its function in aggressive displays and potential role in sexual selection, and also exemplify a very promising approach, that could be applied in field studies of other large mammals. Abstract : The elephant seal proboscis is a textbook case of exaggerated secondary sexual trait with enigmatic function. However, its study is complicated, because it must be analyzed fully expanded during vocalizations. Using field stimulation experiments, photogrammetry, and geometric morphometrics, we show that proboscis morphology can be accurately quantified in naturally behaving wild individuals, allowing us to demonstrate allometric changes even after sexual maturity. This study opens new research avenues and exemplifies a most promising approach in field studies of large mammals.